Comprehensive Review of Universal Challenges in Public Health and Medicine - Al muhri, Rakan Abdullah Mohammed; Al yami, Jamilah Mubarak Saad; Al sharyah, Mahdi Saleh Mahdi; Al Sharyah, Saleh Ali; Alyami, Ali Jarallah Atran; Alsalem, Farhan Yahya; Alsalem, Taleb Yahya; Alyami, Salem Ali; Alyami, Saleha Saeed Marzouq; Al-lajam, Yousef Ahmad Mohammd (Journal of Ecohumanism, 2024)
Education is considered one of the basic human needs; thus, public health and medicine are essential to human lives, while both fields have common issues. So, major trends in healthcare systems are observed: uncertainties and changes that may occur, the burden of diseases and demographics, and health inequity remain today’s major points of reference’ in global health. This review outlines some of the major generalizable issues of concern in global public health and medicine, namely, emerging infectious and chronic diseases, health disparities, health systems, and climate change. Based on literature from diverse parts of the world, this review discusses the present state of the nation’s health systems and their capacity to meet these challenges. Further, it explores the role of international partnerships, policy changes, and technology development in managing such crises. One is aimed at health equity for all citizens of society’s countries, and another focuses on international cooperation and sustainable health care for all.